IMPACT OF HONEY BEE POLLINATION ON POD SET OF MUSTARD (BRASSICA JUNCEA L.: CRUCIFERAE) AT PANTNAGAR - GOSWAMI, VIMLA; M. S. KHAN (The Bioscan, 2013)
The diversity and abundance of different insect visitors on mustard (Brassica juncea) were studied at Pantnagar. A total of 19 insect visitors belonging to order Hymenoptera (15) and Diptera (4) were found to visit the mustard blossoms at Pantnagar. The abundance (percentage of insect/m2/2min.) of Hymenopterans were maximum followed by the Dipterans and others. In Hymenopterans, the honeybees (Apis bees) were observed maximum followed by non Apis bees and the scolid wasp. Insect pollinations increased the number of pods and percent pod set.